KIEDY KOBIECOŚĆ NIE JEST OCZYWISTA – KONTROWERSJE WOKÓŁ PŁCI ZAWODNICZEK W KONTEKŚCIE IGRZYSK OLIMPIJSKICH - Pawlak-Hejno, Elżbieta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is a rethoretical analysis of media coverage on Caster Semenyi published on sports websites such as sport.pl, przegladsportowy.pl and sportowefakty.pl. In 2009 at the World Championships in Berlin, a female athlete who won the race at 800 m. beat her competitors easily. However, her remarkable success was overshadowed by controversy which aroesed over her sex and the need fortests which were supposed to confirm if Caster Semenyi could compete with other women. Her exceptional case attracted both the media’s as well as scientists’ attention. The latter did a discourse analysis concerning her person from different perspectives. In the history of Polish sport the sex of two female Polish athletes: Stanisława and Ewa, has been questioned twice as well. The article is to answer the guestions: how is the controversy concerning Caster Semenyi’s sex presented bu the Internet media and how are two female Polish athletes, whose sex has also been questioned, profiled in this context.